Why to Invest in your Neighbor? Social Contract on Educational Investment - Panu Poutvaara; Vesa Kanniainen (Center for Economic Studies and ifo Institute (CESifo), 1999)
It may be in the interest of low-ability individuals to subsidize the education of high-ability individuals. Sufficient conditions are surprisingly mild: positive externalities in education and complementarity in production between human capital and labor supllied by the low-ability individuals. However, tax competition and the free mobility of the educated give rise to time-inconsistency and free-riding problems which render such a social contract infeasible and result in a subotimally low investment in education.
Keywords: 330; Externalities in education; complementarity; social contract; tax competition